Kevin O’Connell’s North: Modernism, Sibelius, and Identity - McCay, Jennifer (Nordlit, 2020)
The influence of Jean Sibelius and Scandinavian modernism can show up in unexpected quarters: the Northern Irish composer Kevin O’Connell (b. 1958) names the Finnish great as one of his crucial influences, particularly evident in the composition North. Having grown up under the shadows of the Northern Irish Troubles since the late 1960s, O’Connell’s music can be read as a way to engage with this specific identity crisis. Another northern influence on this piece, albeit non-musical in topic, includes Seamus Heaney’s collection of poetry of the same title and structure, with Heaney also hailing from Derry in Northern Ireland.Alongside such issues of identity, this article assesses the determinacy of Kevin O’Connell's orchestral composition, entitled North (1997–98), on Sibelius’s Symphony No. 4. North displays motivic transformation as a significant element of O’Connell’s orchestral style and the central element utilized to construct an extended and coherent piece of music. As mentioned, Sibelius’s influence is not only musical; in his position as a composer from northern Europe negotiating a path between nationalist political movements and the productive engagement with the central European artistic tradition, in the process laying claim to full membership of the exclusive club of European composers – all of which contribute to ‘Conceptualizing the North’.
Keywords: Kevin O'Connell; North; Ireland; Identity; Jean Sibelius; Modernism